A method for separation and purification of mouse splenocytes by density gradient centrifugation. Issue 5 (3rd May 2021) - Lu, Yao; Fu, Chenghao; Xia, Chao; Ma, Shiliang
Abstract: Spleen is an information-rich and easy-accessible peripheral lymphoid organ. It has complex cell composition because of the immunocytes maturity and settle down. Changes of the composition and function of these immunocytes are critical to body immune response. To understand the cell behaviors, specific cell subpopulations are required to be separated without heterogeneity. Density gradient centrifugation is one of the cell separation methods with high throughput. However, the greatest defect of this method is its low cell purity. In this study, the separation conditions of tumor-bearing mouse splenocytes were optimized by separation solutions with different density gradients. After separation, lymphocytes were located at the second layer with the proportion of 84.9%, monocytic-like myeloid-derived suppressor cells (Mo-MDSCs) were located at the fourth layer with the proportion of 54.2% and polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) were located at the sixth layer with the proportion of 85.5%. Cells in different layers were further determined by verifying the gene expression pattern of some chemokine receptors on cell surfaces. Furthermore, this method was also used to separate healthy mouse splenocytes. Therefore, this method will be highly useful to separate mouse splenocytes and has laid a foundation for further research on the changes and roles of immunocytes during the development of cancer.